Effect of polyethylene glycol on the properties of self-curing concrete - V. Jagannadha Kumar, M; Jagannadha Rao, K; Dean Kumar, B; Srinivasa Reddy, V (International Journal of Engineering and Technology, 2018)
Hydration of Portland cement directly effects the development of engineering properties of concrete. It is reported that for sufficient hydration to take place, the relative humidity in the pores needs to be maintained above 80%. It is very important to minimize the loss of moisture from concrete. Curing is the method of regulating the water content of concrete during cement hydration. The objective of this paper is to observe the effect of polyethylene glycol as internal curing agent, on the properties of self-cured concrete of M20, M40 and M60 grades. Compressive, split-tensile and flexural strength properties of self-curing concrete mixes are evaluated and assessment of the quality, structural integrity and compressive strength are made on internally and externally self-cured concrete. The optimum dosage of polyethylene glycol (PEG) (expressed in percentage by weight of cement) adopted for M20, M40 and M60 grades self-cured concrete are 1%, 0.5% and 0.5% respectively. There is a significant increase in the compressive, split-tensile and flexural strength properties self-curing concrete mixes at all ages of curing when compared to normal externally cured concrete mixes of about 5-20% for all the grades considered for study. This improvement could be due to continuous hydration process thus incessant availability of water resulting in less number of pores and voids and stronger bond between the aggregate and cement paste. Non-destruction evaluation studies reveal that all grades of self-curing agent induced concrete are classified as ‘excellent’ concretes in terms of strength and durability point of view due to improved concrete’s pore structure through enhanced hydration and strengthening of interface transition zone.